Comparison of Frequency of Union between Intramedullary Solid Nailing (Sign Nailing) with Cannulated Nailing Via Open Reduction for the treatment of Fracture Shaft of Tibia - Tayyab Hassan, Syed Muhammad (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Fractures involving the shaft of long bones are common worldwide and tibial fractures are among the most common lower limb injuries to be treated by an orthopedic surgeon. The most common fracture of the lower limb occurs at the tibial diaphysis. Aim: To compare the frequency of union between intramedullary solid nailing (SIGN nailing) with cannulated nailing via open reduction for the treatment of fracture shaft of tibia. Study design: The study was a randomized controlled trial conducted at the Department of Orthopedic Surgery, Allied Hospital, Faisalabad, involving 130 patients with closed diaphyseal fracture shaft of tibia and type 1 open fractures. The study lasted six months, from July 1st, 2014, to December 31st, 2014. Patients were divided into two groups: 65 patients in group A underwent solid nailing and 65 patients in group B underwent cannulated nailing via open reduction. The union of bones was assessed on x-rays at six months. The data was analyzed using SPSS version 16, with descriptive statistics, gender, and union of bones presented as frequency and percentage. A P-value less than 0.05 was considered significant. Results: In our study, out of 130 cases (65 in each group), 32(49.23%) in Group A and 30(46.15%) in Group B were between 14 and 30 years of age, while 33(50.77%3) and 35(53.85%) in respective groups were between 31 and 60 years of age. The mean + sd was calculated as 35.38±12.49 and 37.49±12.59, respectively. 50(76.92%) in Group A and 52(80%) in Group B were male, while 15(23.08%) and 13(20%) in respective groups were females. Comparison of frequency of union between intramedullary solid nailing (sign nailing) with cannulated nailing via open reduction for the treatment of fracture shaft of tibia was done which shows union in 51(78.46%) in Group-A and 59(90.77%) in Group-B while remaining 14(21.54%) and 6(9.23%) respectively had non-union, p value was calculated as 0.05 which shows a significant difference. Practical Implication: The study highlights the importance of understanding the age distribution and gender disparities in the treatment of tibial shaft fractures. Patients aged 14-60 are more likely to require treatment, indicating a need for tailored treatment plans. The study also highlights the need for equitable access to care and rehabilitation services for all patients. Conclusion: We concluded that the frequency of union was significantly higher in cannulated nailing via open reduction when compared with intramedullary solid nailing (SIGN nailing) for the treatment of fractured shafts of the tibia.